2019
DOI: 10.29252/aassjournal.7.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 24-Hour Sleep Deprivation on Cognitive and Motor Skills of Male College Students

Abstract: Background. Sleep is assumed to be a critical factor for human physiological and cognitive function. Lack of sleep is a common condition in daily life. Objectives. The purpose of this study was to evaluate the effects of 24-hour sleep deprivation on cognitive and motor skills in university students. Methods. The participants were volunteers that consisted of 290 male students aged 19-25 years. After primary screening, the subjects were randomly divided into two groups of cognitive tests and motor task test. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…5 ). This finding was similar to that of a previous study 65 that reported no significant increase in motor activity under 24 hours of oxidative stress. However, another study 66 reported a finding to the contrary: reduced motor activity in sleep deprivation, including the ability to execute instructions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…5 ). This finding was similar to that of a previous study 65 that reported no significant increase in motor activity under 24 hours of oxidative stress. However, another study 66 reported a finding to the contrary: reduced motor activity in sleep deprivation, including the ability to execute instructions.…”
Section: Discussionsupporting
confidence: 92%
“…The administration of alcohol to SD rats significantly increased motor activity when compared to non-treated sleep deprived rats in the current study. This observation correlates to that of a previous study, 65 which reported that the brain adenosine system represents a common pathway for the effects of ethanol and sleep deprivation on motor activity. Caffeine-treated rats were observed to display increased motor activity when compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sleep deprivation affected trial-to-trial transfer in this study, which may partly be attributed to the interference with the visuomotor memory. Short- or long-term sleep deprivation was found to affect cognitive functions, including reaction time, working memory, and attention [ 27 , 28 ]. For instance, different types of sleep deprivation were reported to exert visual working memory impairment to different degrees [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…All participants engaged in the sleep deprivation protocol within seven days of completing the baseline assessments. Twenty four-hour sleep deprivation protocols have been used extensively to understand the impact of fatigue on cognitive and physical performance (Joo et al, 2012;Trksak et al, 2013;Ghanbari et al, 2019;Ołpińska-Lischka et al, 2020). On the day of the sleep deprivation protocol, participants completed the ARMS and biological measures of readiness (HRV, saliva sample) at home, prior to breakfast.…”
Section: Experimental Protocolmentioning
confidence: 99%